Development Of Instantaneous Fuel Consumption Measuring System Using Arduino - Teoh, Cheng Lay (Universiti Sains Malaysia, 2017)
Instantaneous fuel consumption measurement is playing a key role in combating fuel price hike by allowing drivers to constantly change their driving behavior to obtain lower fuel consumption while driving. This paper introduces a method of measuring instantaneous fuel consumption of a vehicle through pulse wave measurement of the injector signal by using Arduino. The instantaneous fuel consumption measuring system developed is accurate and reliable with a percentage difference between the measured value and actual value to be less than 8.2%. This measuring system is intended to be used in vehicles that do not have a builtin instantaneous fuel consumption measuring system.